THE ADAPTATION OF ENZYMES OF LIPID AND NITROGENOUS METABOLISMS IN RAT UNDER OXIDATIVE STRESS CAUSED BY COBALT AND MERCURY SALTS - Okhrimenko, S.; Gur'eva, N.; Kaliman, P. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology», 2005)
The dynamic effects of cobalt and mercury chlorides on the activity of adipose tissue lipase, β-oxibutyratedehydrogenase and aminotransferases in rat liver were investigated. The activating effects of salts depending on the type of metal and exposure in organism were revealed on the lipase and aminotransferases. At the same time injection of cobalt and mercury chlorides provoked decrease in β-oxibutyratedehydrogenase activity. The revealed shifts in activities of the mentioned enzymes might reflect adaptation of metabolism to oxidative stress.